Operations management for dummies - Anderson, Mary Ann; Consumer Dummies Staff; Anderson, Edward G.; Parker, Geoffrey (Geoffrey G.) (Hoboken NJ John Wiley & Sons, Inc., 2013)
Operations Management For Dummies serves as a resourceful aid for this difficult subject. Tracks to a typical course in operations management or operations strategy, and covers topics such as evaluating and measuring existing systems' performance and efficiency, materials management and product development, using tools like Six Sigma and Lean production, designing new, improved processes, and defining, planning, and controlling costs of projects.
Getting Baseline Data on Performance -- Reducing Inventory without Sacrificing Customer Service -- Managing Inventory across the Supply Chain -- Chapter 9: Planning for Successful Operations -- Planning from the Top Down -- Exploring the Components of an Aggregate Plan -- Considering Materials -- Planning for Services -- Applying Information to the Entire Organization -- Chapter 10: Managing the Supply Chain -- Seeing the Structure of Supply Chains -- Aligning the Supply Chain with Business Strategy -- Exploring the Bullwhip Effect -- Improving Supply Chain Management -- Part III: Improving Operations -- Chapter 11: Becoming Lean -- Evolving to Lean -- Trimming the Fat -- Producing Just in Time -- Seeking the Silver Bullet -- Chapter 12: Managing Quality -- Deciding What Matters -- Recognizing the Value of Quality Addressing Quality Designing for Quality -- Measuring Quality -- Chapter 13: Creating a Quality Organization -- Reaching Beyond Traditional Improvement Programs -- Adding to the Tool Box -- Overcoming Obstacles -- Part IV: Managing Projects -- Chapter 14: Using Communication and Leadership Skills When Managing Projects --Defining Success -- Figuring Out Why Projects Fail -- Laying Out the Project Management Life Cycle -- Leading a Project -- Chapter 15: Estimating and Scheduling Projects -- Estimating Time and Cost -- Working with Uncertainty -- Putting It All Together.
Includes index.
Keywords: Production management; Business logistics